Special issue introduction: Coloniality of power and hegemonic shifts in the world-system - Komlosy, Andrea; Boatcă, Manuela; Nolte, Hans-Heinrich (2016)
Abstract: Introduction to special issue on coloniality of power and hegemonic shifts in the world-system